Heterologous Expression of Recombinant Human Insulin Glargine (hIG) in Methylotrophic Yeast Pichia pastoris - Herawati, Neng; Rubiyana, Yana; Desriani, Desriani; Santoso, Adi (BRIN, 2022)
World health organization (WHO) announced that diabetic patients increased significantly yearly worldwide. Consequently, the need for insulin becomes very large. Pichia pastoris, defined as methylotrophic yeast and a well-known expression and protein production host, is widely used for biopharmaceutical-based drug production. This research aims to synthesize human insulin glargine (hIG) protein in yeast P. pastoris. Human insulin glargine is a group of long-acting analogue insulin.We used a synthetic hIG-encoding gene constructed in frame with the truncated α-factor secretion signal in a pD902 expression vector. Recombinant plasmid pD902-hIG was linearized using Sac1 enzyme and transformed into P. pastoris genome. Multicopy clones were selected on YPDS plates containing Zeocin™ with concentrations of 100; 500; 1,000; and 2,000 µg//mL. Analyses using SDS-PAGE, slot blot, and Western blot showed that recombinant hIG protein had been obtained with a molecular weight of approximately 6,000 Daltons.